2011
DOI: 10.1097/mop.0b013e3283460599
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric rapid fluid resuscitation

Abstract: Rapid fluid resuscitation is most commonly used for children with moderate-to-severe dehydration, or for patients in shock to restore circulation. Concerns regarding potential for fluid overload and electrolyte disturbances and regarding the method of rehydration (i.e., enteral versus parenteral) raise some debate about the safety and efficacy of rapid fluid resuscitation in the pediatric patient. Recent studies show that early, aggressive fluid resuscitation of up to 60 ml/kg within 1-2 h may be necessary to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(3 citation statements)
references
References 44 publications
0
3
0
Order By: Relevance
“…With a lack of evidence of the benefit of permissive hypotension in pediatric patients, the current standard of care is primarily maintaining tissue perfusion with crystalloid boluses until definitive control of hemorrhage is available. [13] Interestingly, a retrospective study by Vella, et al . examined 154 pediatric trauma patients that presented to a level 1 trauma center over one year and found that 70% of patients did not receive a fluid because it was deemed not necessary by the attending ER physician or trauma surgeon.…”
Section: Pediatric Cardiovascular Systemmentioning
confidence: 99%
“…With a lack of evidence of the benefit of permissive hypotension in pediatric patients, the current standard of care is primarily maintaining tissue perfusion with crystalloid boluses until definitive control of hemorrhage is available. [13] Interestingly, a retrospective study by Vella, et al . examined 154 pediatric trauma patients that presented to a level 1 trauma center over one year and found that 70% of patients did not receive a fluid because it was deemed not necessary by the attending ER physician or trauma surgeon.…”
Section: Pediatric Cardiovascular Systemmentioning
confidence: 99%
“…When FEAST was released, rapid, large-volume fluid resuscitation was the norm in paediatric septic shock, and in other conditions involving fluid loss in children 53 . It may be impossible to directly translate the findings of FEAST into practice change internationally; however, as it represents the current purest examination of the effects of FBT in isolation in critically ill children, it should have prompted further investigation into the safety and efficacy of FBT in this population in the developed world.…”
Section: After the Feast A Famine?mentioning
confidence: 99%
“…7,8 However, some patients are unable to tolerate oral rehydration, and IV crystalloid is frequently used. [8][9][10][11] Ketosis may complicate dehydration when illness prevents the intake of adequate carbohydrates, leading to increased free fatty acid breakdown and ketogenesis. 5,12 Ketoacidosis occurs when there is no carbohydrate substrate and thus no insulin secretion, triggering lipolysis and ketogenesis to prevent hypoglycemia.…”
Section: Introductionmentioning
confidence: 99%